Interprofessional Collaboration amongst Healthcare Workers of a Tertiary Hospital in North-Eastern Nigeria - Solomon Daniel Halilu; Afisulahi Abiodun Maiyegun; Joshua Oluwafemi Aiyekomogbon; Yakubu Bababa Shirama; Yahkub Babatunde Mutalub; Funmilayo Jane Oyediji (Nigerian Postgraduate Medical Journal)
Background: Interprofessional collaboration in healthcare is important to optimise healthcare delivery. However, relatively few studies have been conducted on the topic in Nigeria, especially in the North. Objective: The objective of this study was to determine the levels of interprofessional collaboration, enablers and barriers amongst healthcare workers. Materials and Methods: Data were collected using a five-domain modified Assessment of Interprofessional Team Collaboration Scale questionnaire, with a Likert scale of 1–5. The ideal mean score was ≤2 for the barriers domain and ≥4 for the other domains. Data were analysed using the Statistical Package for the Social Sciences (SPSS) version 23. Results: Two hundred and sixty-six participants responded to the questionnaire. Male and female respondents were 131 (49.2%) each. Half of the respondents were 31 to 40 years old. One hundred and thirty-six (51.1%) of the respondents were nurses, and 48 (18.0%) were doctors. The modal working experience was 6–11 years (41.4%), and 117 (44.0%) respondents had at least a bachelor’s degree. The mean scores for the domains were 4.1032 for partnership, 3.2383 for cooperation, 3.6309 for coordination, 4.2844 for enablers and 3.7902 for barriers. Conclusion: There was adequate level of partnership and enablers amongst the healthcare workers but insufficient cooperation and coordination and high level of barriers. Staff training on cooperation, coordination and identified barriers is necessary to improve interprofessional collaboration in the hospital.